Comparison of waste degradation and microbial community profiles during composting of yard waste, kitchen waste and cow manure - Erdem, Elif Irmak. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2017., 2017)
Composting process is an effective low-cost method that converts organic waste including animal manures, municipal biosolids, crop residues, food processing wastes to a valuable resource which can be used as fertilizer and soil conditioner. In this study, two experimental sets named Set1 (Y, K, YKM) and Set2 (YK, YM, KM) were carried out, where the moisture content was adjusted to 55±5 % with the aid of sawdust. Analytical methods were applied to compare the quality of the end products with regulatory requirements to use as soil amendments and to control the process efficiency. Additionally, the bacterial community compositions at thermophilic stage were analyzed using next generation sequencing. Final C/N ratio, volatile solids content, electrical conductivity of all composting systems met with regulatory limitations. The pH in Y and YKM composts were found to be in the range of 5.5 to 8.5 stated in the regulations. Final moisture content was found higher than regulatory limits (<30%) in all systems. The best performance of composting process was observed in Y, K and YK composting systems. Firmicutes and Proteobacteria were the most dominant phylum and the higher abundance of Bacillus sp. in all composting systems indicated very active thermophilic conditions during composting process.
Keywords: Microbial biotechnology.